Street fighters : the last 72 hours of Bear Stearns, the toughest firm on Wall Street - Kelly, Kate, 1975- (New York : Portfolio, 2009)
The shocking fall of Bear Stearns in March 2008 set off a wave of global financial turmoil that continues to ripple. This is the definitive account of a once-great firm's demise, and the human folly that led to the worst financial crisis since the 1930s.
Includes bibliographical references (p. [237]) and index.
Keywords: Bear, Stearns & Co; Investment banking -- United States; Bank failures -- United States; Financial crises -- United States